(3GdQLGds - (3GdMSf Hf Ydj Hf OGhO, Jbqj GdOjf, GdeYQha HGHf OGhO GdMdj,J (B740 (3g` s ((3TQja Hf HgGA GdOjf GdMSfj s)
(3ChdgG (B:s
(3hHYO , aEfj deG fXQJ aj CUhd GdaJGhi GdabgjI EVWQQJ Edi GdCMGOjK GdeQhjI Yf GdCFeI , hGdONhd Hjf eNJdagG Ydi GdWQjbI GdeQVjI s
(3BNQgG (B:s
(3aGWeI HfJ gGQhf MOKfi eMeO Hf CHj YejQ HcJGH YHjOGddg Ydj GdMdHj de jSeY efgG ZjQ gPG s
(3GfXQ Qbe (B761 (3JGQjNs
(3Ydjg oebGHdI SfI (B969(3g`s
(3fSNI KGfjIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs